The Effect of Entrepreneurial Orientation, Working Capital And Market Orientation on The Performance of SMEs - Wayan Ardani; Denok sunarsi (Jurnal Manajemen Industri dan Logistik, 2023)
The purpose of this study was to analyze the effect of entrepreneurial orientation, working capital, and market orientation on the performance of Small and Medium Enterprises (SMEs) in Bali. The type of this research was quantitative method. The size of respondents were 280 SMEs, selected by accidental sampling or the sample was chosen by chance at the location and was considered suitable as a data source. In the questionnaire, there were five choices of scores for each statement that could be chosen according to the actual situation felt by the respondent. The data were analyzed using structural equation modeling analysis with the SmartPLS 4.0 software data processing tool. This study revealed that the entrepreneurial orientation, working capital, and market orientation had a positive and significant effect on the performance of SMEs. Finally, this model helps to determine how entrepreneurial orientation, working capital, and market orientation affect business performances of SMEs